2005
DOI: 10.1111/j.1525-1438.2005.15206.x
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy in advanced ovarian cancer: a case-control study

Abstract: The aim of this study was to compare the outcome of patients with advanced ovarian carcinoma treated with neoadjuvant chemotherapy (NACT) with those treated conventionally with primary debulking surgery. From 1994 to 2003, all consecutive cases of advanced-stage epithelial ovarian carcinoma treated with NACT at the University of Bari were identified. A well-balanced group of women who underwent primary debulking surgery followed by platinum-based chemotherapy was selected as controls. Kaplan-Meier and Cox prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Inciura et al (2006) retrospective analysis of 213 cases ovarian cancer patients received neoadjuvant chemotherapy and 361 patients treated by standard mode therapy, results showed that there was not significant differences between the two groups in OS and PFS (p>0.05). Loizzi et al (2005) founded that the median survival time, median progression free survival time and 3-years survival rate of neoadjuvant chemotherapy patients compared with the standard treatment for patients had no significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…Inciura et al (2006) retrospective analysis of 213 cases ovarian cancer patients received neoadjuvant chemotherapy and 361 patients treated by standard mode therapy, results showed that there was not significant differences between the two groups in OS and PFS (p>0.05). Loizzi et al (2005) founded that the median survival time, median progression free survival time and 3-years survival rate of neoadjuvant chemotherapy patients compared with the standard treatment for patients had no significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…Other retrospective analyses have reported similar findings. [18][19][20][21][22][23][24][25][26][27][28] By contrast, several studies have shown that patients treated with neoadjuvant chemotherapy have a worse survival than those treated with primary surgery. [32][33][34] Overall, controversy remains about the use of neoadjuvant chemotherapy as a first-line treatment strategy for women with newly diagnosed HGSC.…”
Section: Discussionmentioning
confidence: 99%
“…17 Many studies suggest equivalent survival in patients receiving adjuvant versus neoadjuvant chemotherapy. [18][19][20][21][22][23][24][25][26][27][28] Notably, Vergote and colleagues 20 reported the only phase III randomized controlled trial in which patients with advanced-stage HGSC were treated with either primary surgery and adjuvant platinum-based chemotherapy (PCS group) or neoadjuvant platinum-based chemotherapy followed by interval cytoreductive surgery and additional adjuvant chemotherapy (NAC group). Although patients in the NAC group had higher rates of optimal cytoreduction and fewer perioperative complications, this did not translate into improved survival.…”
mentioning
confidence: 99%
“…Results of these studies showed that NAC may increase the number of patients suitable for interval cytoreductive surgery by reducing tumor burden and reducing preoperative morbidity [12][13][14][15][16][17][18][19]. Thus, because of recent advances in chemotherapy, NAC followed by interval debulking surgery and further chemotherapy has become an alternative treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%